Nuevo registro de Plagiomerus diaspidis Crawford en Tamaulipas, México, sobre la escama Diaspis echinocacti (Bouché) - Coronado Blanco, Juana María; Ruíz Cancino, Enrique; Trjapitzin, Vladimir A. (Instituto de Ecología, A.C., 1998)
An encyrtid parasite, Plagiomerus diaspidis Crawford, is a New Record for the State of Tamaulipas, México. This species was found attacking the scale Diaspis echinocacti (Bouché) on Opuntia engelmannii Salm-Dyck, in Cd. Victoria. Data on other species of Plagiomerus are mentioned.